IS THE REINHART-ROGOFF DEBT THRESHOLD APPLICABLE TO ITALY? - Hsing, Yu (American Economic & Social Review, 2020)
This paper employs an extended production function to examine the relationship between central government debt and economic growth in Italy. The results show that the threshold of the central government debt ratio for Italy is estimated to be 105.00%, which is greater than the 90% debt threshold proposed by Reinhart and Rogoff. Besides, a higher growth rate of labor employment or investment/GDP ratio would raise the growth rate. Hence, the debt threshold proposed by Reinhart-Rogoff underestimates the debt threshold for Italy. The finding suggests that the debt ratio of 131.09% in 2019 is well above the debt threshold and is likely to be unsustainable.